German Public Offers Modest Support for NATO Enlargement. - United States Information Agency. Office of Research and Media Reaction.; Fleury, Christopher J.; Sweeney, Anna E.; Smeltz, Dina. (Tufts University. Tisch Library., 2019)
In the midst of budget woes and high levels of unemployment in Germany, the German public expresses limited support for NATO enlargement. Preliminary results from a just-completed USIA survey show great reluctance to increase their country's financial contribution to the alliance in order to cover the cost of enlargement.; Opinion Analysis M-165-97